2003
DOI: 10.1097/01.phm.0000087456.28979.2e
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Insufflation-Exsufflation vs. Tracheal Suctioning via Tracheostomy Tubes for Patients with Amyotrophic Lateral Sclerosis

Abstract: For ventilator-dependent patients with amyotrophic lateral sclerosis, mechanical insufflation-exsufflation via a tracheostomy tube with an inflated cuff may be more effective in eliminating airway secretions than conventional tracheal suctioning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
0
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(62 citation statements)
references
References 15 publications
1
58
0
3
Order By: Relevance
“…It involves the application of cycling positive and negative pressure to the airway, facilitating an effective cough and adequate secretion clearance. Studies examining its home-based clinical effectiveness demonstrate that it is safe and well tolerated [2][3][4] ; creates an increased peak cough flow 2,[5][6][7][8] ; results in reduced hospital stay 9 ; and when used as part of a wider home management protocol involving other therapies, such as noninvasive ventilation, achieves reduced rates of pneumonia and hospital stay. 5,6,10,11 However, there have been comparatively few studies examining the broader impact of home-based MI-E on children and their families.…”
Section: Introductionmentioning
confidence: 99%
“…It involves the application of cycling positive and negative pressure to the airway, facilitating an effective cough and adequate secretion clearance. Studies examining its home-based clinical effectiveness demonstrate that it is safe and well tolerated [2][3][4] ; creates an increased peak cough flow 2,[5][6][7][8] ; results in reduced hospital stay 9 ; and when used as part of a wider home management protocol involving other therapies, such as noninvasive ventilation, achieves reduced rates of pneumonia and hospital stay. 5,6,10,11 However, there have been comparatively few studies examining the broader impact of home-based MI-E on children and their families.…”
Section: Introductionmentioning
confidence: 99%
“…Although many centers worldwide have reported successfully using MIE via noninvasive interfaces to prevent pneumonia and ARF, [40][41][42][43][44][45] only our group 19,20,31 and one other 46 have reported its use via tracheostomy tubes. MIE use with intubated subjects had only been described in our 2010 study 18 and in European subjects with lung disease.…”
Section: Discussionmentioning
confidence: 99%
“…MI-E devices effectively clear secretions in ALS patients [45] and their clinical value can be explained by the fact that they can generate expiratory flows >160 L/min [62]. Recently, it has been also demonstrated that MI-E via a tracheostomy tube is more effective in clearing airway secretions than conventional suctioning in ventilator-dependent ALS patients [63].…”
Section: Timing For Ventilatory Support and Secretion Removalmentioning
confidence: 99%